Impaired glucose metabolism after organ transplantation - M. Sh. Khubutia; O. N. Rzhevskaya; K. E. Lazareva (Трансплантология (Москва))
The mechanisms of the action of immunosuppressive agents and the risk factors for the development of posttransplantation diabetes mellitus and its complications are described.